Adsorption and oxidation of formaldehyde on a polycrystalline Pt film electrode: An in situ IR spectroscopy search for adsorbed reaction intermediates - Zenonas Jusys; R. Jürgen Behm (Beilstein Journal of Nanotechnology, 2014)
As part of a mechanistic study of the electrooxidation of C1 molecules we have systematically investigated the dissociative adsorption/oxidation of formaldehyde on a polycrystalline Pt film electrode under experimental conditions optimizing the chance for detecting weakly adsorbed reaction intermediates. Employing in situ IR spectroscopy in an attenuated total reflection configuration (ATR-FTIRS) with p-polarized IR radiation to further improve the signal-to-noise ratio, and using low reaction temperatures (3 °C) and deuterium substitution to slow down the reaction kinetics and to stabilize weakly adsorbed reaction intermediates, we could detect an IR absorption band at 1660 cm−1 characteristic for adsorbed formyl intermediates. This assignment is supported by an isotope shift in wave number. Effects of temperature, potential and deuterium substitution on the formation and disappearance of different adsorbed species (COad, adsorbed formate, adsorbed formyl), are monitored and quantified. Consequences on the mechanism for dissociative adsorption and oxidation of formaldehyde are discussed.